Domestication Signatures in the Non-Conventional Yeast Lachancea Cidri - Cubillos-Riffo, F; Villarreal-Diaz, P; Pena-Echeverria, T; Urbina, K; Benavides-Parra, J (American Society for Microbiology, 2024)
Evaluating domestication signatures beyond model organisms is essential for a thorough understanding of the genotype-phenotype relationship in wild and human-related environments. Structural variations (SVs) can significantly impact phenotypes playing an important role in the physiological adaptation of species to different niches, including during domestication. A detailed characterization of the fitness consequences of these genomic rearrangements, however, is still limited in non-model systems, largely due to the paucity of direct comparisons between domesticated and wild isolates. Here, we used a combination of sequencing strategies to explore major genomic rearrangements in a Lachancea cidri yeast strain isolated from cider (CBS2950) and compared them to those in eight wild isolates from primary forests. Genomic analysis revealed dozens of SVs, including a large reciprocal translocation (~16 kb and 500 kb) present in the cider strain, but absent from all wild strains. Interestingly, the number of SVs was higher relative to single-nucleotide polymorphisms in the cider strain, suggesting a significant role in the strain’s phenotypic variation. The set of SVs identified directly impacts dozens of genes and likely underpins the greater fermentation performance in the L. cidri CBS2950. In addition, the large reciprocal translocation affects a proline permease (PUT4) regulatory region, resulting in higher PUT4 transcript levels, which agrees with higher ethanol tolerance, improved cell growth when using proline, and higher amino acid consumption during fermentation. These results suggest that SVs are responsible for the rapid physiological adaptation of yeast to a human-related environment and demonstrate the key contribution of SVs in adaptive fermentative traits in non-model species. IMPORTANCE The exploration of domestication signatures associated with human-related environments has predominantly focused on studies conducted on model organisms, such as Saccharomyces cerevisiae, overlooking the potential for comparisons across other non-Saccharomyces species. In our research, employing a combination of long- and short-read data, we found domestication signatures in Lachancea cidri, a non-model species recently isolated from fermentative environments in cider in France. The significance of our study lies in the identification of large array of major genomic rearrangements in a cider strain compared to wild isolates, which underly several fermentative traits. These domestication signatures result from structural variants, which are likely responsible for the phenotypic differences between strains, providing a rapid path of adaptation to human-related environments. © 2023 Villarreal et al.